THE CORRELATION BETWEEN COVID-19 SCREENING RESULTS WITH ANXIETY LEVEL OF PREGNANT MOTHERS IN TAMBAKBOYO HEALTH CENTER - Aris Puji Utami; Harianti (International Journal of Midwifery Research, 2021)
The anxiety of pregnant women has increased during the pandemic, especially whenparticipating in the Covid-19 Screening in the third trimester as a condition for childbirth. Sothis study aims to determine the relationship between the results of Covid-19 screening inpregnant women and the level of anxiety of pregnant women at the Tambakboyo HealthCenter in 2021. The type of research used was analytic with a cross-sectional design. Thepopulation was all pregnant women in the third trimester as many as 85 people. The samplesize was 70 people using the Simple Random Sampling technique. The independent variablewas the results of the Covid-19 Screening in pregnant women and the dependent variable isthe level of anxiety of pregnant women. This study used secondary data, namely the results ofthe Rapid test and primary data using an interview guide. The results of the study showedthat the majority (62.9%) of Covid-19 screening results were non-reactive pregnant women.Almost all (77.1%) pregnant women experienced moderate levels of anxiety and almost all(79.5%) pregnant women with moderate levels of anxiety obtained the results of the rapidtest, which was non-reactive. The results of the Chi-Square test obtained a p-value = 0.533,so there was no significant relationship between the results of the Covid-19 Screening inpregnant women and the level of anxiety of pregnant women. It is hoped that furtherresearchers will research other factors that affect the level of anxiety of pregnant womenduring the pandemic.